Kepercayaan Diri Wanita Menopause - I Wayan Candra (Jurnal Gema Keperawatan, 2015)
This study aims to determine the confidence of menopausal women in the Puskesmas Klungkung I. This research is a descriptive research study in the form of cross-sectional design. The experiment was conducted in Klungkung I Puskesmas in March and ending in July 2014, Consecutive sampling using sampling techniques. The total sample of 50 people. The results obtained confidence  menopausal women most of the 24 people (48%) confidence level of the respondents in the low category. Respondents who have low confidence respectively of 9 people (37.5%) completed primary school and junior high, most of the 18 people (75%) do not work and most of the 18 people (75%) had no income.